c-Myc Overexpression Uncouples DNA Replication from Mitosis - Li, Qing (American Society for Microbiology, 1999)
c-myc has been shown to regulate G(1)/S transition, but a role for c-myc in other phases of the cell cycle has not been identified. Exposure of cells to colcemid activates the mitotic spindle checkpoint and arrests cells transiently in metaphase. After prolonged colcemid exposure, the cells withdraw from mitosis and enter a G(1)-like state. In contrast to cells in G(1), colcemid-arrested cells have decreased G(1) cyclin-dependent kinase activity and show hypophosphorylation of the retinoblastoma protein. We have found that overexpression of c-myc causes colcemid-treated human and rodent cells to become either apoptotic or polyploid by replicating DNA without chromosomal segregation. Although c-myc-induced polyploidy is not inhibited by wild-type p53 in immortalized murine fibroblasts, overexpression of c-myc in primary fibroblasts resulted in massive apoptosis of colcemid-treated cells. We surmise that additional genes are altered in immortalized cells to suppress the apoptotic pathway and allow c-myc-overexpressing cells to progress forward in the presence of colcemid. Our results also suggest that c-myc induces DNA rereplication in this G(1)-like state by activating CDK2 activity. These observations indicate that activation of c-myc may contribute to the genomic instability commonly found in human cancers.